2018
DOI: 10.1080/13647830.2018.1465598
|View full text |Cite
|
Sign up to set email alerts
|

Strain rate and flame orientation statistics in the near-wall region for turbulent flame-wall interaction

Abstract: Flame-wall interaction (FWI) in premixed turbulent combustion has been analyzed based on a counter-flow like configuration at the statistically stationary state. For the present configuration, the two FWI sub-zones, i.e the influence zone and the quenching zone, can be quantified from the DNS results. Detailed analysis of the important quantities, such as the flame temperature, flame-wall distance, wall heat flux, flame curvature and dilatation (including the flame normal and tangential strain rates), and some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The reactive scalar gradient is less preferentially aligned with the compression direction e 3 and more preferentially aligned with the extensive direction e 1 in the flame, which leads to a negative TSI contribution in both cases 3D_R_CP_ST01 and 3D_R_CP_ST10. Such a rotation of the orientation vector in the vicinity of the flame has been previously reported in experimental and numerical studies conducted under different conditions [29,58,52,26]. To assess the physical processes that are responsible for this change of orientation, the budget of the vector n is considered in Fig.…”
Section: Small-scale Turbulence-scalar Interactionsmentioning
confidence: 55%
See 1 more Smart Citation
“…The reactive scalar gradient is less preferentially aligned with the compression direction e 3 and more preferentially aligned with the extensive direction e 1 in the flame, which leads to a negative TSI contribution in both cases 3D_R_CP_ST01 and 3D_R_CP_ST10. Such a rotation of the orientation vector in the vicinity of the flame has been previously reported in experimental and numerical studies conducted under different conditions [29,58,52,26]. To assess the physical processes that are responsible for this change of orientation, the budget of the vector n is considered in Fig.…”
Section: Small-scale Turbulence-scalar Interactionsmentioning
confidence: 55%
“…Whatever the scalar is chemically-reactive (e.g., progress variable) or not (e.g., mixture fraction), its variance as well as the shape of its probability density function (PDF) are indeed settled, to a large extent, by the scalar dissipation rate (SDR), see for instance [15,16,17,18]. The SDR is the product of the scalar diffusivity with the square of the scalar gradient norm [19,20,21] and, the studies reported in references [21,22,23,24,25,26] excepted, it is noteworthy that there were quite few efforts directed towards its detailed analysis in turbulent reactive two-phase flows. Moreover, it should be emphasized that most of the seldom studies that have been conducted in this direction were focused on the direct effect of the additional source terms associated with the evaporation process, see for instance [23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The physical phenomenon in the near wall region during FWI has also been investigated in statistically planar turbulent premixed flames impinging on a flat inert wall at different temperatures by Zhao et al [20][21][22] and for different fuel Lewis numbers by Konstantinou et al [23]. Recent experimental findings for V-flames interacting with cold walls [24][25][26] and transient headon quenching [27] have confirmed the DNS findings regarding the influence of the flame on turbulence and vice verca.…”
Section: Introductionmentioning
confidence: 77%
“…a near wall flame front consists of two parts, the head-on flame part with n • N > 0 and the entrained flame part n • N < 0 with N being the unit wall normal vector. As discussed by Poinsot et al [5] and Zhao et al [9,10], the vortex pair, or if the local flow moves away or towards the wall, determines the evolution and wrinkling of the flame front. Figure 4 shows the joint PDF between the flame-wall distance and the velocity component u 1 at the left side of flame brush edge for the case 8T0.…”
Section: Overall Flame and Flow Structurementioning
confidence: 96%
“…It is found that the terms of the SDR transport equation at the quenching stage near the wall shows distinctly different contribution from that away from the wall. Recently Zhao et al [9,10] introduced a statistically stationary FWI configuration as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%